Poduzeća SUFID i La Dalmatienne od osnutka do Drugoga svjetskog rata crtice iz povijesti elektrifikacije Šibenika i okolice - Anić, Tomislav, povjesničar (2020)
U članku se istražuju okolnosti osnivanja i rad poduzeća SUFID i La Dalmatienne. Poseban naglasak stavljen je na aspekt elektrifikacije Šibenika i njegove okolice s obzirom na ulogu tih pravnih subjekata. Prateći razvoj poduzeća u gotovo polustoljetnom razdoblju od kraja XIX. do prve polovine XX. stoljeća, težište je stavljeno na prepoznavanje važnijih elemenata procesa modernizacije koji su bili izravna posljedica druge industrijske revolucije. Poduzeća su u tom razdoblju bila podložna svim promjenama s obzirom na ekonomske i političke okolnosti.
The history of large industrial companies in the late 19th and first half of the 20th century mirrors the modernity of every society. The goal of this paper is to explore the history of the companies ‘SUFID’ and ‘La Dalmatienne’ in light of those economic and political developments that influenced their work. Based on archival research conducted in the Croatian State Archives and the State Archives in Šibenik, the work of the ‘SUFID’ and ‘La Dalmatienne’ factories in regard to the development of electrification and its consequences are analysed. The focus of study is the production of electrical energy, which made up a significant part of the total production of both companies and greatly changed the life of Šibenik and its surrounding area. Through case studies on the development of the ‘SUFID’ and ‘La Dalmatienne’ companies, some of the more important elements of the functioning of the economy are explained, such as the influence of global economic trends on local economic developments and the influence of international politics on domestic politics, which had a direct impact on the functioning of the economy and the regulation of property-law relations. The consequences of industrialisation, i.e. its direct influence on the immediate surroundings, are also analysed. From the time of early industrialisation, property-law relations were encroached upon, as was the manner of their resolution, in order to pave the way for changes in space needed for the development of infrastructure, especially roads and power transmission line routes.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 456-458.
Sažetak ; Summary.
Keywords: Ekonomska povijest -- Elektrifikacija -- Modernizacija; SUFID -- La Dalmatienne; 19./20. st; Šibenik